2020
DOI: 10.1186/s43066-020-00064-6
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus-induced posterior reversible encephalopathy syndrome presenting as left upper limb monoplegia, convulsions, and sudden blindness: case report

Abstract: Background To report a case of sudden onset left upper limb monoplegia, convulsions, and bilateral blindness in a patient receiving tacrolimus for immunosuppression following living donor liver transplantation (LDLT) consistent with posterior reversible encephalopathy syndrome (PRES). Case presentation We report a case of a 64-year-old male patient on tacrolimus treatment following LDLT. On day 11, during his post-operative routine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The occurrence of PRES in patients after transplantation secondary to tacrolimus is well-documented in the literature. This phenomenon has been observed in patients who have received liver ( 1 4 ), heart ( 5 , 6 ), kidney ( 7 – 9 ), and multivisceral transplants ( 10 ). In a retrospective chart review of 4,222 patients who underwent solid organ transplants, PRES developed in 21 (0.49%) patients ( 11 ).…”
Section: Discussionmentioning
confidence: 87%
“…The occurrence of PRES in patients after transplantation secondary to tacrolimus is well-documented in the literature. This phenomenon has been observed in patients who have received liver ( 1 4 ), heart ( 5 , 6 ), kidney ( 7 – 9 ), and multivisceral transplants ( 10 ). In a retrospective chart review of 4,222 patients who underwent solid organ transplants, PRES developed in 21 (0.49%) patients ( 11 ).…”
Section: Discussionmentioning
confidence: 87%
“…Some unusual clinical presentations like optic neuropathy with monoplegia and convulsions have also been reported. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 It has also been observed that tacrolimus neurotoxicity is not dose related as seen in our patient. 16 , 22 There has been no literature showing association with timing of initiation of CNIs and the occurrence of PRES. The idiosyncratic neurotoxicity can be because of genetic polymorphisms in CYP3A5 that enhance susceptibility to tacrolimus-related neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation